ROCK inhibitors upregulate the neuroprotective Parkin-mediated mitophagy pathway - Natalia Moskal (Nature Portfolio, 2020)
Damaged mitochondria are known to cause neuronal death, suggesting clearance as a potential therapy. Here, Moskal et al. show that ROCK inhibitors promote Parkin recruitment and mitophagy and have neuroprotective effects in fruit flies challenged with a toxin that induces mitochondrial damage.